Psychedelics for Cancer Pain and Associated Psychological Distress: A Narrative Review of a Potential Strategy - Erika Belitzky; Lis Victoria Ravani Carvalho; Melissa Taylor; Cristina Naranjo Ortiz; Laura Baum; David A. Fiellin; Maryam B. Lustberg (Cancer Medicine)
ABSTRACT Purpose To evaluate the current level of evidence for the use of psychedelics for the management of cancer pain and associated psychological distress. Content Pain is a common symptom of cancer and treatment. However, there are high rates of undertreatment of cancer pain due to the complex underlying biology of the condition, and potentially due to a decrease in opioid prescribing in response to the opioid epidemic. A diagnosis of cancer and cancer‐related pain can trigger high levels of psychological distress throughout cancer treatment. Cancer pain can also be exacerbated by anxiety, depression, quality of life challenges, and fear of death and dying, as well as by fear of recurrence or progression. Several pharmacologic and non‐pharmacologic approaches have been utilized to mitigate pain and symptom burden with some success. However, there remains an unmet need for better management of cancer pain and associated symptoms. Psychedelics, such as lysergic acid diethylamide (LSD), psilocybin, mescaline, and N,N‐dimethyltryptamine (DMT), are under consideration as new pharmacologic strategies for mitigating pain and the distress associated with cancer pain and associated symptom burden. Although published studies are limited, regulatory hurdles have decreased. Many clinical trials are underway to assess further the use of psychedelics and behavioral counseling for patients with cancer and comorbidities such as anxiety or depression. These studies examine both the feasibility and efficacy of psychedelics for pain and psychological distress. Early results are promising, and additional research is needed to understand efficacy and tolerability in broader cancer populations. Implications There is an unmet need to improve pain management in patients with cancer and to mitigate psychological distress. Further research is required to understand the efficacy of psychedelics for the treatment of cancer pain and distress. Recent regulatory changes have paved the way for increased research on the clinical efficacy of psychedelics in cancer.